Surfactant Variations in Capsanthin-loaded Nanostructured Lipid Carrier: Formulation, Characterization, and Stability Study - Efiana, Nuri Ari; Shofa-ulhusna, Fatihah; Paramita, Lathifah Aurora; Heavena, Indana Azza; Masyfiyah, Salsabila Fariha; Muhamed, Farahidah; Permadi, Adi; Wahyuningsih, Iis (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2026)
The stability of drugs and nanocarriers is a crucial factor in guaranteeing their efficacy and quality. Nanostructured lipid carriers (NLCs) as lipid-based nanocarriers provide benefits in overcoming the stability and other issues associated with the drug. Surfactants play a crucial role in imparting the desired characteristics of lipid based systems, including stability, particle size, size distribution, and zeta potential. This study aimed to develop a capsanthin-loaded NLC formulation with an optimal surfactant combination that exhibits the required properties and stability. Three formulations were prepared applying Tween 20 and Span 80 in ratios of 5:1, 2:1, and 1:1 for F1, F2, and F3, respectively. Capsanthin, as an active ingredient, originates from paprika powder. NLC properties regarding transmittance, particle size, polydispersity index (PI), zeta potential, loading capacity (LC), and loading efficiency (LE) were characterized. Furthermore, stability studies were also conducted in this research. The results showed that F1 exhibited desirable characteristics, including transmittance percentage, particle size, PI, zeta potential, LC, and LE of 87.22±2.64%, 255.4±46.88 nm, 0.54±0.13, -39.51±3.02 mV, 12.59±0.35%, and 35.40±3.07%, respectively. Moreover, the physical stability studies exhibited that F1 provided a more stable system compared to other formulations. Additionally, the chemical stability indicated that degradation occurred in the paprika powder, not in the NLC. In conclusion, NLC can protect capsanthin, as evidenced by the stable capsanthin levels in NLC compared to those in paprika powder.